Trilateral association of autophagy, mTOR and Alzheimer’s disease: Potential pathway in the development for Alzheimer’s disease therapy - Subramanian, Arunkumar; Tamilanban, T.; Alsayari, Abdulrhman; Ramachawolran, Gobinath; Wong, Ling Shing; Sekar, Mahendran; Gan, Siew Hua; Subramaniyan, Vetriselvan; Chinni, Suresh V.; Izzati Mat Rani, Nur Najihah; Suryadevara, Nagaraja; Wahab, Shadma (Frontiers in Pharmacology, 2022)
The primary and considerable weakening event affecting elderly individuals is age-dependent cognitive decline and dementia. Alzheimer’s disease (AD) is the chief cause of progressive dementia, and it is characterized by irreparable loss of cognitive abilities, forming senile plaques having Amyloid Beta (Aβ) aggregates and neurofibrillary tangles with considerable amounts of tau in affected hippocampus and cortex regions of human brains. AD affects millions of people worldwide, and the count is showing an increasing trend. Therefore, it is crucial to understand the underlying mechanisms at molecular levels to generate novel insights into the pathogenesis of AD and other cognitive deficits. A growing body of evidence elicits the regulatory relationship between the mammalian target of rapamycin (mTOR) signaling pathway and AD. In addition, the role of autophagy, a systematic degradation, and recycling of cellular components like accumulated proteins and damaged organelles in AD, is also pivotal. The present review describes different mechanisms and signaling regulations highlighting the trilateral association of autophagy, the mTOR pathway, and AD with a description of inhibiting drugs/molecules of mTOR, a strategic target in AD. Downregulation of mTOR signaling triggers autophagy activation, degrading the misfolded proteins and preventing the further accumulation of misfolded proteins that inhibit the progression of AD. Other target mechanisms such as autophagosome maturation, and autophagy-lysosomal pathway, may initiate a faulty autophagy process resulting in senile plaques due to defective lysosomal acidification and alteration in lysosomal pH. Hence, the strong link between mTOR and autophagy can be explored further as a potential mechanism for AD therapy.